INTANGIBLE CULTURAL HERITAGE RELATED TO ARTISTIC CRAFTSMANSHIP (Scientific journal of the Fergana State University, 2023)
In this article, the types of intangible cultural heritage related to arts and crafts are discussed in the history of pottery, embroidery, jewelry, goldsmithing, carpet making, knife making, painting, hat making, jewelry making, wood carving, wood carving, and the preservation of historical and cultural values and unique traditions of the people of Uzbekistan, passed down from generation to generation, as well as the transformation processes are discussed.